PENGEMBANGAN E-PUZZLE PECAHAN PADA SISWA KELAS 3 DI SEKOLAH DASAR - Erina Rahma Dhania; Sri Rahayu; Dyah Tri Wahyuningtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of inappropriate learning media can have an impact on the lack of understanding of fraction material. Therefore, this study aims to develop fraction E-Puzzle for 3rd grade students in elementary schools. This study uses Research and Development (R&D) development using the ADDIE model. Data analysis uses qualitative and quantitative methods.  The data collection instruments used were validation sheets from material, media and language experts, student questionnaires, teacher questionnaires, pretest and posttest questions, and interview guidelines. Validation results show that material experts reach 82%, media experts reach 92%, while language experts reach 92%, all three are categorized as very feasible. The pre-test results were 62% and the post-test 85.33%, which showed an increase of 23.33%. Student responses to E-Puzzle reach 90.4%, while teacher responses reach 92%, both are categorized as very good. Thus, E-Puzzle fractions are feasible, practical and effective to improve the learning outcomes of 3rd grade students in elementary schools and can be a solution in overcoming students' difficulties in understanding fraction material.